Population trends in emergency cancer diagnoses: The role of changing patient case-mix - Herbert, A. (Cancer Epidemiol, 2019)
BACKGROUND: Diagnosis of cancer through an emergency presentation is associated with worse clinical and patient experience outcomes. The proportion of patients with cancer who are diagnosed through emergency presentations has consequently been introduced as a routine cancer surveillance measure in England. Welcome reductions in this metric have been reported over more than a decade but whether reductions reflect true changes in how patients are diagnosed rather than the changing case-mix of incident cohorts in unknown. METHODS: We analysed ‘Routes to Diagnosis’ data on cancer patients (2006–2015) and used logistic regression modelling to determine the contribution of changes in four case-mix variables (sex, age, deprivation, cancer site) to time-trends in emergency presentations. RESULTS: Between 2006 and 2015 there was an absolute 4.7 percentage point reduction in emergency presentations (23.8%–19.2%). Changing distributions of the four case-mix variables explained 19.0% of this reduction, leaving 81.0% unexplained. Changes in cancer site case-mix alone explained 16.0% of the total reduction. CONCLUSION: Changes in case-mix (particularly that of cancer sites) account for about a fifth of the overall reduction in emergency presentations. This would support the use of adjustment/standardisation of reported statistics to support their interpretation and help appreciate the influence of case-mix, particularly regarding cancer sites with changing incidence. However, most of the reduction in emergency presentations remains unaccounted for, and likely reflects genuine changes during the study period in how patients were being diagnosed.